Factors Affecting Behavior for Preventing Covid-19 Infection When Working on Employees During A Pandemi at Puskesmas Balai Agung, Sekayu District in 2021 - Rizka Muliani; Ririn Noviyanti Putri; Heru Listiono; Sutriyati; Nurrahmah Romadhona (Institute of Computer Science (IOCS), 2022)
COVID-19 is a disease caused by the Novel Coronavirus (2019-nCov) or SARS-CoV-2. The highest cases were recorded in Sekayu District, where there were 811 positive confirmed cases, 14 deaths and 711 recovered cases. For an addition of 12 positive confirmed cases. Cases of COVID-19 infection in Indonesia, including cases of health workers and non-health workers exposed to COVID-19 infection, continue to increase in health care facilities. From this data, researchers are interested in researching